Retrospective review of the clinical case of a radical correction of the transposition of the great vessels, complicated by mediasthenitis and sepsis - Rakhima Mekenbayeva (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2019)
In the century of advanced technology, medicine has leaped forward, which contributed to the possibility of correcting such severe congenital heart defects in children as the transposition of great vessels. However, despite the progress in medicine and compliance with the rules of asepsis and antisepsis, infection of the postoperative wound remains one of the frequent and terrible postoperative complications, worsening the prognosis and increasing the risk of mortality. In this retrospective analysis, we consider a clinical case of a radical correction of the great vessels transposition with a complication that has arisen (wound infection) in the early and late postoperative period. The relevance of the article lies in the fact that we studied international experience in managing patients with this complication and applied it in this clinical case in a child with transposition of great vessels, who underwent several cardiac and thoracic operations complicated by wound infection, sepsis, DIC-syndrome with significant deficit bone skeleton of the chest. The child’s condition improved significantly: infectious complications were stopped, signs of heart failure decreased. The child is observed for 7 years, the observation will continue.